Model Tests on the Retaining Walls Constructed from Geobags Filled with Construction Waste - Hua Wen; Jiu-jiang Wu; Jiao-li Zou; Xin Luo; Min Zhang; Chengzhuang Gu (Advances in Materials Science and Engineering)
Geobag retaining wall using construction waste is a new flexible supporting structure, and the usage of construction waste to fill geobags can facilitate the construction recycling. In this paper, model tests were performed on geobag retaining wall using construction waste. The investigation was concentrated on the slope top settlement, the distribution characteristics of the earth pressures on retaining walls and horizontal wall displacements, and slope failure modes. The results indicated that the ultimate loads that the slope tops with retaining walls could bear were 87.5%~125% higher than that of the slope top without retaining walls. The ultimate loading of strengthened slopes with different slope ratios from 1 : 0.75 to 1 : 0.25 could be reduced by 11.8% to 29.4%. The horizontal displacements of the retaining walls constructed from geobags were distributed in a drum shape, with the greatest horizontal displacements occurring about 1/3~1/2 of the wall height away from the bottom of the wall. As the slope ratio increased, the failure of the slope soil supported by geobag retaining wall using construction waste changed from sliding to sliding-toppling (dominated by sliding) and then to toppling-sliding (dominated by toppling). The range of 1/3~1/2 of wall height is the weak part of the retaining walls, which should be strengthened with certain measures during the process of design and construction.